Efecto de estrategias pedagógicas mediadas por los códigos QR para el fortalecimiento de la atención sostenida (2018)
This research seeks to determine the effect of pedagogical strategies mediated by QR codes on the strengthening of sustained attention, taking into account the importance of care for the development of academic processes and how the current generation relates to the new technologies. The study was conducted at the Jaipris Educational Center in the city of Barranquilla. It is based on the theories of, Shulman (1986), Camacho, Flórez, Gaibo, et al (2012), Siemens (2004) and Mirsky and Duncan (2001), which give a concise and coherent support to each one of the variables of this research, being these pedagogical strategies mediated by ICT and sustained attention. To achieve this goal, this was carried out from an empiricist-inductive epistemological approach, with the positivist paradigm, under the quantitative method, a pre-experimental design and a scope of descriptive research. The population under analysis is the students of the Jaipris Educational Center located in the southwest of Barranquilla, selecting as sample the 18 students of 4th grade of primary school. For the analysis and collection of the information, the d2 test was used, which would answer the hypothesis. Based on the results obtained, it is possible to establish the pertinence and feasibility of this research, since it was possible to verify that there is an effect of the pedagogical strategies mediated by QR codes on the strengthening of sustained attention